2014
DOI: 10.1186/1745-6215-15-337
|View full text |Cite
|
Sign up to set email alerts
|

Tai chi mind-body exercise in patients with COPD: study protocol for a randomized controlled trial

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is a chronic, progressively debilitating condition that is prevalent in the US and worldwide. Patients suffer from progressive dyspnea and exercise intolerance. Physical exercise is beneficial, but conventional pulmonary rehabilitation programs are underutilized. There remains a need for novel interventions that improve symptoms, quality-of-life, and functional capacity. Tai chi is an increasingly popular mind-body exercise that includes physical exercise,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 90 publications
(79 reference statements)
0
19
0
2
Order By: Relevance
“…The Tai Chi intervention is designed specifically for an older, physically limited population with COPD [54,79,80]. The structured intervention emphasizes essential Tai Chi movements that are easily comprehensible and can be performed repetitively in a flowing manner.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tai Chi intervention is designed specifically for an older, physically limited population with COPD [54,79,80]. The structured intervention emphasizes essential Tai Chi movements that are easily comprehensible and can be performed repetitively in a flowing manner.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the five formal movements, the intervention includes a complementary set of traditional Tai Chi warm-up exercises which focus on loosening the physical body, incorporating mindfulness and imagery into movement, promoting overall relaxation, and coordinating breathing awareness. Four traditional interrelated breathing techniques are integrated into the training regimen and coordinated with physical movements [80]. Chairs will be provided for tai chi exercises that are performed in a seated position and resting, as well as for stability as needed when performing other exercises.…”
Section: Methodsmentioning
confidence: 99%
“…Both the active mind-body intervention and the comparator group (conventional pulmonary rehabilitation) need to be standardized. Most studies have been conducted in Chinese populations, and several studies are under way to test these interventions in Western populations to increase generalizability 113130…”
Section: Chronic Obstructive Pulmonary Disease and Pulmonary Rehabilimentioning
confidence: 99%
“…A number of components of TC may be relevant to the treatment of deconditioned, pulmonary patients with COPD (eg, physical exercise, breathing training, mind-body awareness, stress management), 19 20 however, there have been few large-scale studies of TC in COPD. One recent, randomised controlled trial (RCT), conducted in China, reported TC was equivalent to pulmonary rehabilitation for improving health-related quality of life (HRQL) at 12 weeks.…”
Section: Introductionmentioning
confidence: 99%